Strategi Humas Universitas Negeri Makassar Dalam Meningkatkan Citra Positif Masyarakat - Risma Niswaty; Sri Wulandari; Sirajuddin Saleh; Muh. Rizal S (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2018)
This study aims to determine the public relations strategy of Makassar State University in increasing the positive image of Makassar State University in the community. To find out these objectives, the researchers used a type of qualitative descriptive research. The informants in this study were as many as five people using data collection techniques carried out through observation, interviews and documentation. Data obtained from research results are processed using data analysis techniques consisting of data reduction, data presentation and conclusion drawing. The results showed that Public Relations devised a strategy so that the function could run in accordance with the objectives of Makassar State University, among others, trying to create a conducive climate between institutions and the public in order to do persuasive and educative approaches to the public, trying to create two-way communication by disseminating information from institutions to public parties. educate and provide information, in order to create mutual understanding, respect, understanding and also strive to foster harmonious relations between organizations and various groups, both in and out relations to enhance cooperation. Public Relations seeks to socialize the Makassar State University mission to be accepted or received support from the public / public.